2014
DOI: 10.1002/app.40815
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity against Escherichia coli of Cu‐BTC (MOF‐199) metal‐organic framework immobilized onto cellulosic fibers

Abstract: A strong antimicrobial activity against Escherichia coli of Cu‐BTC metal‐organic frameworks immobilized over cellulosic fibers is hereby reported. The in situ synthesis of Cu‐BTC metal‐organic frameworks, aka MOF‐199 or HKUST‐1, onto cellulosic substrates was carried out by exposing carboxymethylated cellulosic substrates to Cu(OAC)2, 1,3,5‐benzenetricarboxylic acid and triethylamine solutions following a very specific order. Using an in vitro model, in accordance to ASTM E2149‐13a, we observed that the cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(82 citation statements)
references
References 18 publications
3
77
1
1
Order By: Relevance
“…The antibacterial mechanism of this compound is related to the release of Cu and after destroying the wall and membrane and entering the cell, an enzymatic activity is targeted in the bacterium, which ultimately leads to a reduction in gene expression (26,27 (28,29). Similar to previous studies (30)(31)(32)(33), the present study found that the antibacterial activity of nanostructures includes metal/metal oxide copper. The real-time PCR method is sensitive and commonly used to detect gene expression.…”
Section: Discussionsupporting
confidence: 86%
“…The antibacterial mechanism of this compound is related to the release of Cu and after destroying the wall and membrane and entering the cell, an enzymatic activity is targeted in the bacterium, which ultimately leads to a reduction in gene expression (26,27 (28,29). Similar to previous studies (30)(31)(32)(33), the present study found that the antibacterial activity of nanostructures includes metal/metal oxide copper. The real-time PCR method is sensitive and commonly used to detect gene expression.…”
Section: Discussionsupporting
confidence: 86%
“…The Cu 2? ions in HKUST-1 possessed the cytotoxicity against bacteria, which might destroy the structure of bacterial cell membrane via transforming membrane proteins and fatty acids or altering transmembrane potential to make an adverse impact on the growth and reproduction of bacteria (Rodriguez et al 2014). When microorganisms contact with the HKUST-1/CF composite, Cu 2?…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Based on the recognized ability of HKUST-1 to capture gases and toxic chemicals, combined with Cellulose the availability of cellulose-based fibrous materials, the described procedure provided the basis for future fabrication of functionalized fibers and active filtration media. Rodriguez et al (2014) in situ synthezed HKUST-1 onto carboxymethylated cellulosic fabrics, and they observed that the cellulose-MOF system was able to completely eliminate the growth of Escherichia Coli (E. coli) on agar plates and liquid cultures. Lange and Obendorf functionalized cotton fibers by partial etherification and self-assembly of polyoxometalate (POM, [CuPW 11 O 39 ] 5-) encapsulated in Cu 3 (BTC) 2 metal-organic framework (HKUST-1) (Lange and Obendorf 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also bear the ability to systematically vary and functionalize their pore structure [2,3]. In the history of MOFs, a benchmark was represented by the synthesis of MOF-5 (Zn 4 O(bdc) 3 , bdc = terephthalate) and HKUST-1 (Cu 3 (btc) 2 , btc = 1,3,5-benzenetricarboxylate) with high porosity and low pressure gas sorption, followed by the development of chromium(III) terephthalate (MIL-101) with high chemical stability, MOF-74 (Zn 2 (dhbdc), dhbdc = 2,5-dihydroxy-1,4-benzenedicarboxylate) with low pressure adsorption of CO 2 , and several isostructural analogs of Mg-MOF-74 termed as IRMOF-74-I to IRMOF-74-XI, with large pore apertures to accommodate protein, NU-110E with acetyleneexpanded hexatopic linker, having material highest experimental Brunauer-Emmett-Teller (BET) surface area of any porous material reported to date (7140 m Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. …”
Section: Introductionmentioning
confidence: 99%